-0.87y+2=y-0.6

Simple and best practice solution for -0.87y+2=y-0.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.87y+2=y-0.6 equation:


Simplifying
-0.87y + 2 = y + -0.6

Reorder the terms:
2 + -0.87y = y + -0.6

Reorder the terms:
2 + -0.87y = -0.6 + y

Solving
2 + -0.87y = -0.6 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
2 + -0.87y + -1y = -0.6 + y + -1y

Combine like terms: -0.87y + -1y = -1.87y
2 + -1.87y = -0.6 + y + -1y

Combine like terms: y + -1y = 0
2 + -1.87y = -0.6 + 0
2 + -1.87y = -0.6

Add '-2' to each side of the equation.
2 + -2 + -1.87y = -0.6 + -2

Combine like terms: 2 + -2 = 0
0 + -1.87y = -0.6 + -2
-1.87y = -0.6 + -2

Combine like terms: -0.6 + -2 = -2.6
-1.87y = -2.6

Divide each side by '-1.87'.
y = 1.390374332

Simplifying
y = 1.390374332

See similar equations:

| -40=-8(8-m) | | -6(x-9)=-42 | | 7+8(4+4x)=6x-39 | | -8a+6a+42=1 | | 4x-3(x-1)=-4+3x+11 | | Fx=10x^2+8x+8 | | 22/2= | | 3x(x^2+2x-6)+4(x^2-6x+2)= | | g(x)=3.4x-8 | | 20n=10n^2 | | 2.2m=19.8 | | 13x+5=-35 | | 6=2(v+8)-4v | | 4(6y+1)+8=6(2y+5)-5 | | 0.9(5x+15)2.5-(x+3)= | | x^6+8y^3= | | (12y^3)+(24y^2)=3y+6 | | X+2x+(2x+30)=280 | | -x=4x-3 | | 4+3x-2=8x+18-3x | | -8=-8(2x-7) | | 93=(93)(63) | | st+3y=6 | | 8-3(1-3m)= | | 1.8+7n=9.5-4bn | | 0.60p+80=0.70+30 | | 2(6x-2)=3(5x-5) | | 6y^2+1y-2=0 | | Y=157.5x+50 | | 0.8y=-4 | | [-5/8][-8/15]= | | 1=-1.5+0.5y |

Equations solver categories